KATEGORI NON-MUSLIM PERSPEKTIF AL-QUR’AN - Haniru, Rahmad (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Discussion of the al-Qur’an on a problem is very unique and special, it is not like science books. Al-Qur’an is also rarely presents a problem in detail. Discussion of the al-Qur’an generally global. Non-Muslims in the al-Qur’an called by the term kafir, musyrik and ahl al-kitab. From the information of the al-Qur’an obtained an explanation that predicate kafir looks explicitly presented to ahl al-kitab, while the predicate of musyrik be vague, because if it is reviewed from attitude and behavior of ahl al-kitab, impressed they belong in the category of musyrik, but that thing not revealed in the al-Qur’an explicitly. Analyze about categories non-Muslims perspective of the al-Qur’an, won’t be perfect, if the research is only focused to just one or two verses which discusses non-Muslims, because of that way will give to a partial opinion, not in accordance with the purpose of understanding the category of non-Muslim from the perspective of the al-Qur’an, especially if the analysis is done regardless of the context of the verse, history, asbab al-nuzul, Prophet’s explanation, and others, which has been collected by commentators al-Qur’an. This research is normative research with primary legal materials, secondary and tertiary with descriptive data analysis. By using the approach interpretation of the al-Qur’an and linguistics, the writer did content analysis to the category of non-Muslims from the perspective of the al-Qur’an. Research results show that, non-Muslims in the perspective of the al-Qur’an mentioned in several terms, that is: kafir, musyrik and ahl al-kitab. The research results too revealed that, turned out to be peoples musyrikun and ahl al-kitab both identified as peoples kafir. Whereas ahl al-kitab, although in general declared to have committed shirk, but they don’t strictly given the predicate of musyrik